Maternal Obesity Alters Neurotrophin-Associated MAPK Signaling in the Hypothalamus of Male Mouse Offspring - Bae-Gartz, Inga; Janoschek, Ruth; Breuer, Saida; Schmitz, Lisa; Hoffmann, Thorben; Ferrari, Nina; Branik, Lena; Oberthuer, Andre; Kloppe, Cora-Sophia; Appel, Sarah; Vohlen, Christina; Dötsch, Jörg; et al. (Frontiers in Neuroscience, 2019)
Purpose: Maternal obesity has emerged as an important risk factor for the development of metabolic disorders in the offspring. The hypothalamus as the center of energy homeostasis regulation is known to function based on complex neuronal networks that evolve during fetal and early postnatal development and maintain their plasticity into adulthood. Development of hypothalamic feeding networks and their functional plasticity can be modulated by various metabolic cues, especially in early stages of development. Here, we aimed at determining the underlying molecular mechanisms that contribute to disturbed hypothalamic network formation in offspring of obese mouse dams. Methods: Female mice were fed either a control diet (CO) or a high -fat diet (HFD) after weaning until mating and during pregnancy and gestation. Male offspring was sacrificed at postnatal day (P) 21. The hypothalamus was subjected to gene array analysis, quantitative PCR and western blot analysis. Results: P21 HFD offspring displayed increased body weight, circulating insulin levels, and strongly increased activation of the hypothalamic insulin signaling cascade with a concomitant increase in ionized calcium binding adapter molecule 1 (IBA1) expression. At the same time, the global gene expression profile in CO and HFD offspring differed significantly. More specifically, manifest influences on several key pathways of hypothalamic neurogenesis, axogenesis, and regulation of synaptic transmission and plasticity were detectable. Target gene expression analysis revealed significantly decreased mRNA expression of several neurotrophic factors and co-factors and their receptors, accompanied by decreased activation of their respective intracellular signal transduction. Conclusion: Taken together, these results suggest a potential role for disturbed neurotrophin signaling and thus impaired neurogenesis, axogenesis, and synaptic plasticity in the pathogenesis of the offspring’s hypothalamic feeding network dysfunction in maternal obesity.